1954
DOI: 10.1021/ja01633a041
|View full text |Cite
|
Sign up to set email alerts
|

Heterocyclic Vinyl Ethers. IV. Benzo-1,4-oxathiadiene and Benzo-1,4-dithiadiene1,2

Abstract: Vol. 76 ether layer was separated and the aqueous layer extracted with 6 portions of 25 ml. of ether. Removal of the solvent after drying gave a residue which was distilled to give a yellow liquid, b.p. 102-105°(4.5 mm.), 3.5 g. (20%). A large tarry residue was left in the distilling flask. Redistillation gave 3.0 g. (17%), n26D 1.5122, d2i. 0.9646, of 2-Ndimethylammo-4-butylpyrimidine. On standing in a closed flask for 24 hours this compound turns red.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1966
1966
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…To the best of our knowledge, the few existing synthetic procedures are dated, with harsh reaction conditions or troublesome work-up, and almost exclusively directed to 2-substituted derivatives (Scheme 1). [6][7][8][9][10][11][12][13] The first synthetic work 6 for the obtainment of this class of compounds concerns non-substituted 1,4-benzoxathianes (Scheme 1-A); Parham and coworkers used a strong-base catalysis, sodium methoxide, and yielded the desired and unstable products with only poor yields. This initial synthetic pathway was then fully overcome in the following years by one-pot procedures 7,8 (Scheme 1-B), in which suitably substituted cyclohexanones were treated with 1,2mercaptoethanol and a bromine source (NBS or CuBr2).…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, the few existing synthetic procedures are dated, with harsh reaction conditions or troublesome work-up, and almost exclusively directed to 2-substituted derivatives (Scheme 1). [6][7][8][9][10][11][12][13] The first synthetic work 6 for the obtainment of this class of compounds concerns non-substituted 1,4-benzoxathianes (Scheme 1-A); Parham and coworkers used a strong-base catalysis, sodium methoxide, and yielded the desired and unstable products with only poor yields. This initial synthetic pathway was then fully overcome in the following years by one-pot procedures 7,8 (Scheme 1-B), in which suitably substituted cyclohexanones were treated with 1,2mercaptoethanol and a bromine source (NBS or CuBr2).…”
Section: Introductionmentioning
confidence: 99%
“…It was also found that decreasing CuI-L5 catalyst loading from 20 mol% each of CuI and L5 to 10 mol% each of CuI and L5 reduced the yield drastically (entry 14) and other Cu : L5 ratios also reduced the yields of the cyclized product 7 (entry 15). In the absence of CuI or L5 or both, the reaction did not afford even trace amount of coupling product (entries [16][17][18]. It is important to mention that both Cu salt and ligand are mandatory for coupling reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Conventionally, 1,4-benzoxathiine motifs are synthesized by the treatment of 2-mercaptophenol with 1,2dibromoethane in presence of sodiumethoxide [16]. 1,4benzoxathiine moieties are also synthesized by multistep reaction [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Compound 4a [17] was obtained by oxidation of related benzoxathiine 3 [7]. Bromination of 4a resulted in the formation of 6-bromo compound 4b, and nitration gave a mixture of two isomers 4c and 5 in approximately 4:1 ratio [18].…”
Section: Resultsmentioning
confidence: 99%